2017
DOI: 10.4236/wsn.2017.98014
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling Strategies and Throughput Optimization for the Uplink for IEEE 802.11ax and IEEE 802.11ac Based Networks

Abstract: The new IEEE 802.11 standard, IEEE 802.11ax, has the challenging goal of serving more Uplink (UL) traffic and users as compared with his predecessor IEEE 802.11ac, enabling consistent and reliable streams of data (average throughput) per station. In this paper we explore several new IEEE 802.11ax UL scheduling mechanisms and compare between the maximum throughputs of unidirectional UDP Multi Users (MU) triadic. The evaluation is conducted based on Multiple-Input-Multiple-Output (MIMO) and Orthogonal Frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Figures 9 and 10 show the expected throughput gain of D/UL MU transmission based on (3), (4), and (5) varying BSR, MCS level, and the number of interfering STAs. Note that the physical data rate values for calculating the throughput with various numbers of STAs and MCS level are referenced in [17]. The elongated delay issue caused by the neighboring STAs results in time loss for data transmission and reception of STA as shown in Figures 7 and 8.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 9 and 10 show the expected throughput gain of D/UL MU transmission based on (3), (4), and (5) varying BSR, MCS level, and the number of interfering STAs. Note that the physical data rate values for calculating the throughput with various numbers of STAs and MCS level are referenced in [17]. The elongated delay issue caused by the neighboring STAs results in time loss for data transmission and reception of STA as shown in Figures 7 and 8.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…For example, the authors of [16] proposed a scheduling scheme in IEEE 802.11ax with TWT to efficiently handle MU transmissions and multi-AP cooperation. The authors in [17] explored several new IEEE 802.11ax UL scheduling mechanisms and compared them among the maximum throughput of MU. They conducted evaluations of MIMO and OFDMA transmissions in IEEE 802.11ax against the carrier-sense multiple access with collision avoidance (CSMA/CA) MAC of IEEE 802.11ac with the SU and MU modes for various numbers of STAs scenarios in both reliable and unreliable channel environments.…”
Section: Related Workmentioning
confidence: 99%
“…Various schedulers for 802.11ax have been designed and investigated under different channel and traffic conditions to use the 802.11ax capabilities fully. In [ 20 ], multi-user uplink transmissions are considered. It is shown that 802.11ax outperforms 802.11ac in terms of throughput and latency.…”
Section: Related Workmentioning
confidence: 99%
“…For example, the authors of [ 16 ] proposed a scheduling scheme in IEEE 802.11ax with TWT to efficiently handle MU transmissions and multi-AP cooperation. The authors in [ 17 ] explored several new IEEE 802.11ax UL scheduling mechanisms and compared them among the maximum throughput of MU. They conducted evaluations of MIMO and OFDMA transmissions in IEEE 802.11ax against the carrier-sense multiple access with collision avoidance (CSMA/CA) MAC of IEEE 802.11ac with the SU and MU modes for various numbers of STAs scenarios in both reliable and unreliable channel environments.…”
Section: Related Workmentioning
confidence: 99%
“…Figure 9 and Figure 10 show the expected throughput gain of D/UL MU transmission based on (3), (4), and (5) varying BSR, MCS level, and the number of interfering STAs. Note that the physical data rate values for calculating the throughput with various numbers of STAs and MCS level are referenced in [ 17 ]. The elongated delay issue caused by the neighboring STAs results in time loss for data transmission and reception of STA as shown in Figure 7 and Figure 8 .…”
Section: Performance Evaluationmentioning
confidence: 99%